Light curing units in the undergraduate dental clinics: 7 years of follow-up - Esteves Barata, Terezinha Jesus (2021)
Objetive: To monitor the light curing units available at undergraduate dental clinics of a Brazilian Public Higher Education Institution for seven uninterrupted years. Materials and methods: In the period between 2011-2017, the quality control of light curing units at the Faculty of Dentistry, Federal University of Goiás, was evaluated by analyzing their state of conservation and power density (mW/cm2). Data obtained were subjected to descriptive statistical analysis and Levene, Shapiro-Wilk, Kruskal-Wallis, Dunn and Chi-square tests (P <0.05). Results: Regarding the conservation status of the light curing units, comparatively, there was no statistically significant difference between the years 2012, 2016 and 2017 (p> 0.05). Statistically significant differences were found for power density values between years (p <0.0001). In pairwise comparisons, the power density values for the years 2011 (p <0.01) and 2012 (p <0.05) were statistically different from the years 2015, 2016 and 2017. Conclusions: A significant improvement in the state of conservation of light curing units was observed in the initial four years of evaluations, with a decline in the fifth year and stabilization in the last two years. Regarding the power density of the light curing units, a gradual increase was observed in the seven years of study, with stabilization of the results after the fifth year of quality control.